Clinical introduction and benefits of non-invasive ventilation for above C3 cervical spinal cord injury - Toki, Akiko; Nakamura, Takeshi; Nishimura, Yukihide; Sumida, Mikio; Tajima, Fumihiro (The journal of spinal cord medicine, 2021)
Study design: Retrospective study. Objectives: To determine the best time to introduce non-invasive ventilation (NIV), clinical effectiveness of NIV, and complications of long-term use of NIV in patients with high-level cervical spinal cord injuries (CSCI). Setting: Public Hospital, Japan. Methods: The subjects were 14 tracheostomy ventilator-dependent patients, with above C3 spinal lesions, and American Spinal Cord Injury Association Impairment Scale A (ASIA A). They were referred to our clinic between 2005 and 2010 for switching mechanical ventilation support system from tracheostomy ventilation to NIV. Respiratory function tests were measured before and after NIV. Patients who were successfully switched to NIV were interviewed two years later and asked about their health and social status. Results: Eleven patients were successfully switched to NIV. The success rate of switching to NIV within 1 year was also high (P < 0.05). NIV improved the vital capacity of C2 ASIA A and C1 ASIA A patients with adequate respiratory accessory muscle strength sufficient to expand the chest wall. The time on ventilator-free spontaneous breathing increased or did not deteriorate after NIV. Three C1 ASIA A patients with insufficient muscle strength to expand the thorax mastered glossopharyngeal breathing and enjoyed a short ventilator-free time. All patients who were successfully switched to NIV lived in the community. Two patients developed minor complications after discharge and two died later for unrelated causes. Conclusion: Ventilator-dependent patients should be switched to NIV within 1 year of injury. Long-term NIV can improve respiratory function and clinical outcome.